Making Each Drop Count - Anil Kumar Singh, (Journal of Soil and Water Conservation, 2022)
Water is an abundant natural resource as three fourth’s of the earth’s surface is covered with it but only 2.7 per cent of the global water available is fresh water and less than one per cent of the total is available to meet the water demands of the human and livestock population both of which are increasing in an alarming manner. The rest of the fresh water is locked up in glaciers and snow cover. The fact is that on 2.3 per cent of the world’s land, India supports almost 17 per cent of the world’s population with only 4 per cent of the world’s fresh water resources. Not only the per capita land availability but also the per capita water availability is decreasing day by day. Per capita water availability was more than 5300 m3 in 1951, had decreased to 1905 m3 in 1999 and is likely to be less than 1500 m3 by 2025. In the Indian sub-continent barring a few river basins like Brahamaputra & Barak, Narmada and a couple of others, all others would either be water stressed (per capita water availability between 1700 -1000 m3) or water scarce (per capita water availability